Vasectomy reversal and prostate cancer risk: A multi-centre collaborative demonstration project of the Intentional Population Data Linkage Network: Letter to the International Journal of Population Data Science. (2018) - Boyd, James; Randall, Sean; Fuller, Emma
No abstract available